Assessment of probiotic properties of lactic acid bacteria isolated from an artisanal Colombian cheese (2023)
Lactic Acid Bacteria play an important role in the milk fermentation processes of traditional cheeses and have become an important target for the development of novel cheese cultures because of their ability to confer health benefits. This study aimed to evaluate the probiotic potential of 12 Lactic Acid Bacteria (LAB) strains previously isolated and molecularly identified from an artisanal Colombian Double-Cream Cheese. Probiotic properties, including safety (hemolysis and sensibility to antibiotics), pH and bile salt tolerance, auto-aggregation, cell surface hydrophobicity, antibacterial activity, and exopolysaccharide production, were examined. None of the strains were hemolytic, and Pediococcus (16, 18) and Lactobacillus (28, 29) were found to be sensitive to all antibiotics. Moreover, all the strains tolerated pH (3.0, 6.5 and 8.0) and bile salt conditions (0.3, 0.6 and 1.0 % w/v). Pediococcus pentosaceus (16), Leuconostoc citreum (17), Pediococcus acidilactici (18), Enterococcus faecium (21,22), Enterococcus faecalis (24) and Limosilactobacillus fermentum (29) exhibited medium autoaggregation and affinity to chloroform. Six of the strains exhibited a ropy exopolysaccharide phenotype. Antibacterial activity against foodborne pathogens, Salmonella Typhimurium ATCC 14028, Listeria monocytogenes ATCC 19111, Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923, was found to be strain dependent, with the strains 16, 18, 21, 26, 28 and 29 presenting a higher inhibition (>4 mm) against all of them. According to Principal Component Analysis, P. pentosaceus (16), Leu. mesenteroides (26), L. casei (28), L. fermentum (29), and E. faecium (21) showed strong probiotic properties. Our findings suggest that five strains out of the 12 sampled strains are potential probiotics that could be used in the processing of traditional dairy products on an industrial scale to improve their quality.